Allotransplantation of Cryopreserved Testicular Tissue as the Way to Correct Rabbit Testes Hypofunction - Grischenko, V. I.; Chadayev, V. E.; Volina, V. V. (Problems of Cryobiology and Cryomedicine, 2009)
The effect of cryopreserved testicular tissue allotransplantation on the rabbit’s testes morphofunctional state under sexual abstinence conditions has been studied. Obtained the data testify to the fact, that after testicular tissue allotransplantation there is the recovery of spermatogenic epithelium and spermatogenesis renewal in testicular parenchyma of male rabbits, kept without females within 2 months under sexual abstinence conditions.